A digital maintenance practice framework for circular production of automotive parts - Turner, Christopher J.; Okorie, O.; Emmanouilidis, Christos; Oyekan, J. (Elsevier, 2020)
The adoption of the Circular Economy paradigm by industry leads to increased responsibility of manufacturing to ensure a holistic awareness of the environmental impact of its operations. In mitigating negative effects in the environment, current maintenance practice must be considered, not just for the reduction of its own direct impact but also for its potential contribution to a more sustainable lifecycle for the manufacturing operation, its products and related services. Focusing on the matching of digital technologies to maintenance practice in the automotive sector, this paper outlines a framework for organisations pursuing the integration of environmentally aware solutions in their production systems. This research acts as a primer for digital maintenance practice within the Circular Economy and the utilisation of Industry 4.0 technologies for this purpose
Keywords: Maintenance models and services; Intelligent maintenance systems; Sustainability